A Global Overview of the Schemes of Extraction of Pillars in Major Coal Producing Countries - Kumar, Sikandar; Sinha, Rabindra Kumar; Jawed, Mohammad (Journal of Mines, Metals and Fuels, 2023)
Seams amenable to open cast mining is on the verge of exhaustion globally and to meet the future demand of coal, underground mining method is the only viable technique left. In India, also quite a large number of coal seams have been extensively developed and standing on pillars for a long time. Extraction of these standing pillars with reasonable safety has been a challenge to mining engineers for most of reasons. Presently, depillaring in Indian mines is mostly carried out through cyclic unit operations involving drilling, blasting, loading with either a Side Discharge Loader (SDL) or a Load Haul Dumper (LHD), transport and hauling. Fully mechanized depillaring panels are limited in number. Mechanized depillaring using Continuous Miner and shuttle car is being used in a few mines in India with a view to achieving bulk production and high productivity. Still we are far behind with our Output per Man Shift (OMS), to a tune of 2.01 compared to the global OMS of 12 tonnes per man-shift in depillaring districts. Different strata, along with hostile geo-mining factors, are considered to be this prime case of low productivity. This paper seeks to highlight the existing depillaring practices in India and other major coal-producing countries namely USA, Australia and South Africa. The authors also present a case study on conventional depillaring practice in the Indian context and a few methods being practiced in major coal-producing countries.